The role of compliance in the operation of credit institutions - Pelei, Andrea; Benedek, Petra (Public Finance Quarterly, 2024)
The aim of this article is to present a conceptual framework for compliance with legal and ethical standards in the business environment, with a particular focus on the role and current challenges of internal control. The paper describes systems and methods for developing effective compliance risk management strategies. The paper presents the importance of an organization’s internal control systems through a literature review. It shows how compliance tools can be used to prevent harmful processes and how to deal with abuses such as money laundering. Finally, the article outlines new compliance challenges, such as the indirect effects of the Russia-Ukraine war and the challenges of implementing sanctions.